O możliwości zastosowania algorytmu genetycznego w prognozowaniu - Romowicz, Anna (About Possible Application of Genetic Algorithms for Prediction, 2006)
In this article there is shown example of using Holt model prediction with three parameters (α, ß,γ) where parameters are estimated by procedure used genetic algorithm. Using this method emerged from the fact that parameters (α, ß, γ) should be chosen to minimize mean error of prediction. First of all. the model should follow values changes in time, secondly should distinguish between incidental changes of incoming series and permanent changes of prediction values. Proposed method is based on idea of estimation primary values of parameters by using genetic algorithm and then optimization with exponential smoothing Holt's formula completed with new mechanism.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 103-111